Left Anterior Descendent Coronary Artery Fistula to Main Pulmonary Artery with Triple Vessel Disease:A Report of Two Cases - Lyndon Darwin; Yan Efrata Sembiring; Oky Revianto Sediono Pribadi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Coronary artery fistula is a rare anomaly of coronary artery. It represents connection between one or more ofcoronary arteries and cardiac chamber or great vessel. It can also cause significant hemodynamic changes. Toreport cases of left anterior descending coronary artery (LAD) fistula to main pulmonary artery (MPA) withconcomitant triple vessel disease.Case 1 was 59-year old male presented with intermittent chest discomfortfor a year. Echocardiogram showed severe MR with cleft at A1 and A2 and coronary angiogram resultshowed LAD fistulation to MPA. Case 2 was 57-year old male presented with chest discomfort and at the leftshoulder. Echocardiogram showed trivial MR and coronary angiogram showed triple vessel disease alongwith tortuous fistulation of LAD to MPA. Both patients underwent teflonpledget-reinforced direct suturingof fistula origin and 3-grafts coronary artery bypass graft. Patient no 1 also underwent mitral annuloplastyand valvuloplasty.Post-operative period was uneventful and both patients were discharged after 17 days and5 days respectively. Short term follow-up showed improvement of symptoms and no residual fistulation.Inshort term follow-up teflonpledget-reinforced direct suturing of coronary fistula origin result satisfactory.Larger study and further follow up is necessary.